The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00405-014-3269-y
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness topical amphotericin B in the management of chronic rhinosinusitis: a meta-analysis

Abstract: Chronic rhinosinusitis (CRS) is believed to be the result of an exaggerated reaction to fungi in the nasal mucosa, and topical amphotericin B (AMB) is a commonly used treatment. The purpose of this study was to perform a meta-analysis of high-quality comparative studies to examine the efficacy of topical AMB for the treatment of CRS. A search was conducted of Medline, Cochrane, EMBASE, and ISI Web of Knowledge until December 31, 2013 using combinations of the search terms chronic rhinosinusitis, human, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Other controversies include total dosage, treatment duration, and the route of administration. The daily dose ranged from 3 to 20 mg of AMB, and the treatment duration ranged from 4 to 80 weeks . In our present study, a daily dose of 20 mg of AMB was applied, the same as that in our previous study .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other controversies include total dosage, treatment duration, and the route of administration. The daily dose ranged from 3 to 20 mg of AMB, and the treatment duration ranged from 4 to 80 weeks . In our present study, a daily dose of 20 mg of AMB was applied, the same as that in our previous study .…”
Section: Discussionmentioning
confidence: 99%
“…Across different research groups, the methodology of AMB application varies regarding delivery technique, drug concentration, and daily dose . Two recent meta‐analyses reported that topical AMB was not beneficial for CRS . Among the 5 randomized controlled studies enrolled for meta‐analyses, different AMB concentrations had been applied for treatment of CRS.…”
mentioning
confidence: 99%
“…37 Multiple meta-analyses looking at topical antifungal treatment with amphotericin B included several RCTs that met inclusion criteria. 38,39 Results indicated no differences between treatment and placebo groups for quality of life, nasal endoscopy, or symptom scores. In a meta-analysis pooling five studies investigating topical and one study investigating systemic antifungal agents, symptom scores statistically favored placebo, and adverse event reporting was higher in the antifungal group.…”
Section: Topical Anti-fungal Agentsmentioning
confidence: 95%
“…Nearly all have evaluated topical amphotericin, but one recent RCT used topical fluconazole and also found no benefit . Multiple meta‐analyses looking at topical antifungal treatment with amphotericin B included several RCTs that met inclusion criteria . Results indicated no differences between treatment and placebo groups for quality of life, nasal endoscopy, or symptom scores.…”
Section: Introductionmentioning
confidence: 99%
“…In the EPOS and in a recent review article by Wang et al [149], the recommendation to not use topical amphotericin B is made This is based on the fact, that five RCTs were unable to demonstrate a positive outcome in nasal endoscopy or in the culture of fungi from the nasal mucosa.…”
Section: Types and Therapies Of Rhinosinusitismentioning
confidence: 99%